The Application of Regression Model on Human Resource Data to Improve Workforce Productivity at STIE Wikara - Adam, Duki; Najmudin (Awatara Publisher, 2024)
The application of regression models in human resource data analysis has become a vital approach in increasing labor productivity in various educational institutions, including at the Wikara College of Economics (STIE). The aim of this research is to test whether human resource management influences workforce productivity at STIE Wikara. This research is quantitative research. This research was conducted at STIE Wikara Purwakarta. The population of this research is all 54 employees of STIE Wikara Purwakarta who are also the samples in this research. The results obtained indicate that human resource management influences work productivity. However, further research is still needed by adding other variables to strengthen this study, as well as by focusing on different objects and subjects compared to this research.